The Effects of Activation Treatments for Crumb Rubber on the Compatibility and Mechanical Performance of Modified Asphalt Binder and Mixture by the Dry Method - Liang, Ming; Qiu, Zhengmei; Luan, Xuehao; Qi, Cong; Guo, Ning; Liu, Zhaoxin; Su, Linping; Yao, Zhanyong; Zhang, Jizhe (Frontiers in Materials, 2022)
Compatibility and mechanical performance of crumb rubber (CR) modified asphalt and mixture prepared by dry method are poor at present, which limits the application of dry mixed asphalt rubber in paving engineering. To solve this problem, various activating treatment for CR were performed and the modified asphalt binder was prepared by dry process in this study, aiming to activate the CR modifier and improve the compatibility of CR asphalt blends. The effects of pre-treating methods of high temperature, pre-swelling and microwave treatment on rutting resistance and compatibility of asphalt binder and asphalt mixture were evaluated. Furthermore, the dynamic shear rheometer (DSR) of temperature sweep, Brookfield rotary viscosity, the physical properties, rutting resistance and microstructure of modified asphalt were measured. The results indicated that the activated CR increases the high temperature performance of the CRMA binder in dry process. The high-temperature and microwave pre-treating for CR lead to the largest of complex modulus, viscosity and rutting factor. Moreover, high-temperature, pre-swelling and microwave treatment for CR significantly increase the dynamic stability of dry mixed asphalt mixtures, which indicates the enhanced resistance to permanent deformation. In microscopy, homogeneous and compatible state were obtained for asphalt modified by high temperature treated CR and pre-swelled CR, in which the strong interaction occurs among rubber molecule and asphalt component. The microstructure of dry CR asphalt blends shed light on the mechanical performance. Consequently, activated CR modification for asphalt binder by dry process in this study is a promising technology and other properties need be to verified in future.